2018
DOI: 10.1016/j.chest.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Clusters Predict Outcomes in a Longitudinal Interstitial Lung Disease Cohort

Abstract: Among adults with diverse chronic ILDs, cluster analysis using baseline characteristics identified four distinct clinical phenotypes that might better predict meaningful clinical outcomes than current ILD diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Previous studies have reported a wide range of figures for the prevalence of progressive disease in patients with ILDs, reflecting the different cohorts studied and the variety of criteria used to define progression. However, it is clear that a sizeable minority of patients with CTD-ILDs, chronic HP, iNSIP, sarcoidosis-ILD and unclassifiable IIP develop a progressive fibrosing phenotype characterized by decline in lung function, worsening symptoms and premature death 4,5,7,25,27,28,[32][33][34][35] . The physicians who participated in this survey estimated that patients with non-IPF progressive fibrosing ILDs die approximately 4-5 years after initial diagnosis of ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a wide range of figures for the prevalence of progressive disease in patients with ILDs, reflecting the different cohorts studied and the variety of criteria used to define progression. However, it is clear that a sizeable minority of patients with CTD-ILDs, chronic HP, iNSIP, sarcoidosis-ILD and unclassifiable IIP develop a progressive fibrosing phenotype characterized by decline in lung function, worsening symptoms and premature death 4,5,7,25,27,28,[32][33][34][35] . The physicians who participated in this survey estimated that patients with non-IPF progressive fibrosing ILDs die approximately 4-5 years after initial diagnosis of ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Although some patients with chronic HP experience partial recovery, patients with chronic fibrosing HP may experience rapid disease progression, particularly if the inciting antigen cannot be identified and removed [32,33]. In a recent longitudinal cohort analysis, the monthly decline in FVC % predicted over 1 year in 119 patients with chronic HP was similar to that of 286 patients with IPF [34]. In patients with stage IV pulmonary sarcoidosis, both increases and decreases in FVC and DLco may be observed over time as the disease relapses and remits [35].…”
Section: Lung Function Decline In Progressive Fibrosing Ildsmentioning
confidence: 99%
“…Investigations about the role of both genetic and environmental factors have also been conducted and showed that FOXP3 polymorphisms might determine the susceptibility IIP or CTD‐ILD in Chinese Han population and African‐American race refers to a younger age at ILD diagnosis and a better survival . A new cluster analysis among adults with various chronic ILD has been conducted, and four distinct clinical phenotypes were identified, allowing a better prediction of clinical outcomes than the current ILD diagnostic criteria. Having been said that genetic and environments are considerable impacting ILD epidemiology and natural history, we must not forget the role of co‐morbidities due to their impact on worsening of patient’s survival as seen in recent works conducted in Denmark and Germany along with the role of histopathological findings on disease progression …”
Section: Interstitial Lung Diseasementioning
confidence: 99%